2014
DOI: 10.1007/s12524-014-0397-1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Cherry Leaf Chlorophyll Concentrations Based on Foliar Reflectance Spectra Variables

Abstract: This paper assesses the capability of hyperspectral remote sensing to estimate chlorophyll a (Chl a), chlorophyll b (Chl b), and chlorophyll a + b (Chl a + b) concentration at cherry leaf scale using a variety of spectral variables during the growth season. A field experiment was conducted in cherry orchard. The leaf reflectance spectra of cherry plants were acquired within 350-1050 nm wavelengths. A variety of spectral variables were mathematically computed based on the leaf spectra and transformation of refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…of stomata/cm 2 ; S I = { S /( E + S )} × 100, where S = number of stomata for unit area, E = number of epidermal cells per unit area. For chlorophyll estimation, 0.5 g fresh leaf sample was extracted in 80% acetone (25 mL) and estimated spectrophotometrically at 645 and 663 nm after 48 h dark incubation at 4 °C [30].…”
Section: Methodsmentioning
confidence: 99%
“…of stomata/cm 2 ; S I = { S /( E + S )} × 100, where S = number of stomata for unit area, E = number of epidermal cells per unit area. For chlorophyll estimation, 0.5 g fresh leaf sample was extracted in 80% acetone (25 mL) and estimated spectrophotometrically at 645 and 663 nm after 48 h dark incubation at 4 °C [30].…”
Section: Methodsmentioning
confidence: 99%
“…About 0.2 g apple leaves were cut from each leaf sample for grinding in 6 mL 95% alcohol with a small amount of quartz sand and calcium carbonate powder, until the grinding blade into liquid, then filtered by adding alcohol for a total of 25 mL in each tube [20]. Each sample for analysis of chlorophyll concentration was placed in a cuvette and absorbance was measured between 200 nm and 1000 nm with 2.0 nm wavelength accuracy and 1nm wavelength repeatability using a UV-2100 UV/V is Spectrophotometer [21]. For each sample, three replicates were analyzed.…”
Section: Chemical Analysis Of Chlorophyll Concentrationsmentioning
confidence: 99%
“…Jin et al analyzed the spectrum of rice leaves and the corresponding chlorophyll content and found that the sensitive bands related to the chlorophyll content of rice leaves were 450-686 and 750-780 nm [10]. Lu et al analyzed the correlation between the spectrum of cherry leaves and chlorophyll content after making various changes [11]. Using stepwise linear regression analysis, it was found that the variable log(1/R741) was highly correlated with the chlorophyll of cherry leaves.…”
Section: Introductionmentioning
confidence: 99%